The spurious relationship between moral blameworthiness and liability for negligence - Goudkamp, J (University of Melbourne, 2004)
Traditional learning maintains that liability for negligence is ultimately premised on notions of moral blameworthiness. It is thought that the legal principles which define the scope of negligence loosely conform to such notions. This article challenges that view. While there is a certain amount of evidence which supports the conventional view it is argued that this evidence is eclipsed by many important instances where the tort of negligence is insensitive to considerations of moral blameworthiness.